Impact of Demonetization on E-Commerce Industry: Analyzing the impact of demonetization on the online shopping industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The move of 'Demonetization' by the Hon'ble Prime Minister of India, Mr. Narendra Modi influenced everyone on November 08, 2016. It came about into a frenzy circumstance since individuals were shy of money in their grasp. Demonetization affected web shopping at introductory stage yet later the online merchants saw complex increment in their deals and income. The results of this prompted the utilization of advanced installments and online exchanges in pretty much all aspects of the nation. This move likewise expanded the utilization of advanced and versatile wallets offered by different organizations and banks. It is otherwise called pulling back of a specific type of cash from dissemination. Government pulled the old Rs 500 and Rs 1,000 notes unavailable for general use. While the phenomenal move made by the Prime Minister Narendra Modi has affected internet business and at similar occasions it affects the customers and their shopping conduct through web based shopping. In this manner it becomes important to think about the effect of demonetization on online business industry. The primary point of the examination is to comprehend and dissect the impact of demonetization on buyer's recurrence of purchasing item and customer's method of installment mode through web based shopping post demonetization.